1971
DOI: 10.1126/science.172.3989.1263
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Abnormal Cerebroside Sulfate Metabolism in Cultured Metachromatic Leukodystrophy Fibroblasts

Abstract: Cultured fibroblasts derived from patients with late infantile metachromatic leukodystrophy incorporated arylsulfatase A from the growth medium. Upon exposure to cerebroside sulfate, they exhibited patterns of uptake and hydrolysis indistinguishable from cells derived from control subjects. Furthermore, inclusion granules formed in the metachromatic leukodystrophy fibroblasts upon exposure to sulfatides were cleared by subsequent supplementation of the growth medium with arylsulfatase A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…For example, a-Gal A constitutes approximately 0.002% of total cellular protein in human lung, the source used for enzyme purification. Furthermore, the fact that lysosomal hydrolases turn over slowly in tissues (33,34) leads one to predict that the corresponding mRNAs will be present at disproportionately lower concentrations in poly(A)+ mRNA preparations used to make cDNA libraries. Indeed, the cDNA clone corresponding to another lysosomal hydrolase, a-fucosidase, is among the rarest cloned to date, with an mRNA abundance of 0.002% and a protein concentration of 0.01% of liver protein (27).…”
Section: Resultsmentioning
confidence: 99%
“…For example, a-Gal A constitutes approximately 0.002% of total cellular protein in human lung, the source used for enzyme purification. Furthermore, the fact that lysosomal hydrolases turn over slowly in tissues (33,34) leads one to predict that the corresponding mRNAs will be present at disproportionately lower concentrations in poly(A)+ mRNA preparations used to make cDNA libraries. Indeed, the cDNA clone corresponding to another lysosomal hydrolase, a-fucosidase, is among the rarest cloned to date, with an mRNA abundance of 0.002% and a protein concentration of 0.01% of liver protein (27).…”
Section: Resultsmentioning
confidence: 99%
“…Analyses of Fabry fibroblasts after exposure to enzyme revealed that under the conditions described, a-galactosidase activity rose from near 0 to the hydrolysis of 0.2 pxaol galactose/mg protein/hr, which is the mean activity of the native a-galactosidase in fibroblasts (Table I). In contrast to studies with arylsulfatase A [19], the ficin a-galactosidase was fairly rapidly inactivated within the (Fig. 3) indicated a slightly higher stability for the intracellular a-galactosidase but over 50% of the enzymic activity was lost between 6 and 24 hr after addition of a-galactosidase.…”
Section: Uptake Of Argalactosidase By Fibroblastsmentioning
confidence: 54%
“…Fibroblasts have been used as a model for enzyme replacement in the severe neurologic disease, metachromatic leukodystrophy (MLD) [19,25], and arylsulfatase A activity was then measurable for several weeks in culture. However, MLD fibroblasts do not normally accumulate sulfatide, necessitating the addition of sulfatide to the medium before the enzyme replacement.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly, only 1-5% of normal cellular enzymatic activity was needed to correct the abnormal accumulation of lysosomal substrate. 17,96,104 Starting in the 1970s, ERT clinical trials were performed by infusing normal human enzymes into individuals who had a variety of LSDs, including Sandhoff disease (␤-hexosaminidase A derived from urine), 61 Pompe disease (placental ␣-glucosidase), 28 Fabry disease (placental, plasma, and splenic ␣-galactosidase A), 14 and Gaucher disease Type 1 (placental acid ␤-glucosidase). 13 These studies showed both evidence of substrate degradation and rapid clearance of the intravenously delivered enzymes, but no significant clinical benefits.…”
Section: Enzyme Replacement Therapymentioning
confidence: 99%